Telemonitoring Perkecambahan Benih Jati Emas Dengan Induksi Medan Magnet Statis - Mila Kusumawardani; Zulfa Anggraini Kusumaningtyas; Farida Arinie; ridho hendra yoga perdana (Indonesian Society of Applied Science (ISAS), 2021)
In the cultivation of teak plants often have problems because teak seeds have a thick and hard skin or impermiabel (difficult to penetrate) to water and gas so as to slow germination. The magnetic field can increase the growth rate in inactive seed seeds because the magnetic field affects the physical and chemical properties of water as a germination medium. Water exposed by the magnetic field can be absorbed easily with tissues in the seeds, thus shortening seed dormancy and increasing the percentage of seed germination. This study aims to understand the growth process of dormancy seed germination, To know the influence of magnetic fields on the growth of teak seed seeds, as a solution to the problem of seed dormancy in teak seed seeds. Therefore, the method used in this study is to provide exposure to teak seeds and make tools for monitoring teak growth in real time with the parameters of planting media moisture (to see the absorption of water) and high seeds (for the growth of teak seeds), so that used YL69 sensor for soil moisture and sharp infrared sensor gp2y0a02yk0f for high plants.